Frida Kahlo : her life, her work, her home - Mora, Francisco de la (Art masters (London, England), 2023)
"Frida Kahlo, remembered as one of the most inspiring personalities of the 20th century, was a woman of two intertwined parts: she was both a charismatic and empowered artist exploring themes of resistance, authenticity, cruelty, and suffering, and a more private person whose wounded body caused her a lifetime of pain that underpinned the many successes and disappointments that marked her time in the world. Revealing and exploring these two Fridas, Francisco de la Mora's graphic biography - completed with the endorsement and support of the Frida Kahlo Museum in Mexico City - vividly documents the landscapes and environments that inspired her, the dreams and nightmares that drove her, and the many people she loved. It is also a joyously beautiful tribute to her life, her work, her home - and her art."--